How to be a successful form tutor - Marland, Michael (Continuum, 2004)
At the core of every subject teacher's role is the task of being a tutor. The authors provide an accessible and realistic guide to this vital role based on many years of headship and pastoral care experience. Brimming with practical suggestions and innovative ideas, this guide covers topics such as managing tutorial sessions, relating to families, dealing with bullying, and getting to know your pupils, the book brings together the deeper aims of pastoral care with the daily routines and demands of school life.